PAYMENTS FOR HOSPITALIZATION FOR CONGENITAL SYPHILIS IN CHILDREN UNDER ONE YEAR OF AGE - Carvalho, Leila Maria Cereta de; Santos, Vilma Constancia Fioravante dos; Machado, Maria da Graça Pimenta; Ramos, Adriana Roese (Cogitare Enfermagem, 2024)
Objective: To analyze the financial transfers of authorizations for hospital admissions for Congenital Syphilis in children under one year of age in Rio Grande do Sul, Brazil, from 2012 to 2022. Method: Cross-sectional study with information from Hospital Admission Authorizations from the Hospital Information System on the TabNet Platform (DATASUS). The data was analyzed using descriptive and frequency statistics. Results: There was an increase in the proportion of hospital admissions for congenital syphilis in the universe of infectious and parasitic diseases in children under one-year-old, amounting to an increase of 201.7%. As a result, there was an increase in the number of financial transfers. However, the nominal values were out of line when adjusted for inflation. It was found that 10 days of hospitalization were maintained. Conclusion: The results suggest an urgent need to update the financial resources passed on by the SUS for hospital admissions, as well as the creation of cost-effective actions aimed at reducing hospitalizations for Congenital Syphilis.